The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1007/s11524-017-0160-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Prevalence of Suicide Attempts among Victims of Police Violence in the USA

Abstract: Recent evidence suggests that police victimization is widespread in the USA and psychologically impactful. We hypothesized that civilian-reported police victimization, particularly assaultive victimization (i.e., physical/sexual), would be associated with a greater prevalence of suicide attempts and suicidal ideation. Data were drawn from the Survey of Police-Public Encounters, a population-based survey of adults (N = 1615) residing in four US cities. Surveys assessed lifetime exposure to police victimization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 24 publications
6
85
0
Order By: Relevance
“…We also have no information on the nature of the encounter-whether, for instance, it involved the use of force or whether the person was treated fairly. Recent work has documented that perceived fairness and violence are mechanisms by which policing can affect health (DeVylder et al, 2017;Geller et al, 2014). In addition, concentrated police stops, especially in disadvantaged Black communities, likely increase feelings of powerlessness, strain the relationship between police and the public, and diminish perceptions of gains made by the civil rights movement-all of which can help explain why being stopped by police is related to poor mental health (Alang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also have no information on the nature of the encounter-whether, for instance, it involved the use of force or whether the person was treated fairly. Recent work has documented that perceived fairness and violence are mechanisms by which policing can affect health (DeVylder et al, 2017;Geller et al, 2014). In addition, concentrated police stops, especially in disadvantaged Black communities, likely increase feelings of powerlessness, strain the relationship between police and the public, and diminish perceptions of gains made by the civil rights movement-all of which can help explain why being stopped by police is related to poor mental health (Alang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While there is some variation with regard to outcomes and patterns of association in prior research, police stops have been linked to worse health at both the individual and the aggregate level. A comprehensive survey of adults in Baltimore, New York City, Philadelphia, and Washington, DC, found that virtually all forms of police violence-psychological, physical, sexual, and neglectful treatment-were related to psychological distress and depression (DeVylder et al, 2017). Two studies based in New York City have documented similar results.…”
Section: Policing and Healthmentioning
confidence: 93%
“…22 We recently showed in the Survey of Police-Public Encounters that police-initiated violence is widely reported across 4 US cities, and that it is associated with both psychological distress and depression, 23 as well as more severe mental health outcomes including suicide attempts. 24 Given that the prevalence of police violence in US cities appears to be comparable to other potential social defeat exposures and has known associations with mental health outcomes, it is reasonable to hypothesize that it may likewise be correlated with PEs in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of trauma with intent to harm as a risk factor for psychosis bears resemblance to findings from the suicide literature, which have linked suicidal behavior to specifically assaultive violence, across a broad range of study populations and types of violence exposures (Wilcox et al 2009;Nrugham et al 2010;Coid et al 2013;DeVylder et al 2017). This is notable given the amassing evidence over the past several years that psychotic experiences are robust indicators of risk for suicidal behavior in both cross-sectional and longitudinal epidemiological data, including suicidal ideation, attempts, and death by suicide (Sharifi et al 2015;Honings et al 2016).…”
mentioning
confidence: 59%